PERENCANAAN BAHASA INDONESIA PADA SETIAP JENJANG PENDIDIKAN BERBASIS KURIKULUM 2013: IMPLEMENTASI DAN TANTANGANNYA - Lilis Amaliah Rosdiana; Dadang Sunendar; Vismaia Sabariah Damaianti (STKIP Siliwangi, 2021)
The unquestionable privilege of the bahasa Indonesia from elementary school to university still requires carefull planning in its practice learning. Language planning of bahasa Indonesia is various development processes to strengthen its position an function as the national and official language of this country. Bahasa Indonesia was a language of instruction in learning activities. Supposedly, in the world of education, the empowerment of bahasa Indonesia as a science can be felt clearly, directly and right on target. From aforementioned description, this research is aimed to discover how the implementation of bahasa Indonesia language planning on every level class of education is, 2013 Curriculum. In data analysis, the authors use qualitative approach with descriptive analysis techniques. In the next process, the descriptive method is applied as an attempt to provide an overview, or describe the research objectives. The result shows that the implementation of Indonesia languange planning have basically been going well. This is proven by the existence of plans in the curriculum: however, there is still one challenge i.e. teenagers who prefer to speak foreign language in their daily lives. Thus, this sould be an important concern for teachers, so that language planning of bahasa Indonesia can be clearer and more focused.